Serum Lactate Dehydrogenase Activity and Visceral Organs and Body Weights of Diabetic Rats Administered Single and Combinatorial Herbal Formulations - Chikezie, Chiwendu Maureen; Ojiako, Okey Alphonsus; Emejulu, Adamma Angela; Chikezie, Paul Chidoka (Pharmacognosy Communications)
Background and Aim: The present study evaluated serum lactate dehy- drogenase (LDH) activity. Visceral organs and body weights were used as measures of the capacities of single and combinatorial herbal formulations of Acanthus montanus, Asystasia gangetica, Gongronema latifolium and Solanum melongenas to ameliorate systemic toxicity, visceral organs in- flammation or necrosis and body tissues wasting in alloxan-induced diabe- tes mellitus (DM) rats. Materials and Methods: Alloxan-induced DM rats with fasting plasma glucose concentration (FPGC) > 5.71 mmol/L for 5 con- secutive days were selected for the study. A total of 102 male Wistar rats were divided into seventeen (17) groups of six (6) rats each. Serum LDH activity and body weights and weights of visceral organs and were measured using standard methods. Results: Serum LDH activities of herbal treated rat groups varied within a relatively narrow range of 549.9 ± 12.10 – 500.6 ± 12.02 IU/L and were significantly lower (p < 0.05) than the untreated DM rat group. The body weights of the experimental rat groups after herbal treatment were significantly higher (p < 0.05) than their corresponding weights before herbal treatment. The ratios of liver weights to body weights were within the range of 0.0293 ± 1.4 x 10-3 – 0.0597 ± 2.3 x 10-3. The ratio of kidney weight to body weight of untreated DM rat group was 1.64 fold higher than that of normal rat group (p > 0.05). Conclusion: Overall, 200 mg/kg body weight double herbal formulations of A. gangetica + A. montanus and A. gangetica + G. latifolium offered the greatest therapeutic benefits to alloxan-induced DM rats, with respect to all diagnostic parameters considered in the present study.
Keywords: Body weights; Diabetes mellitus; Herbal formulations; Lactate dehydrogenase; Visceral organs.